2017
DOI: 10.18632/oncotarget.18899
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperones in the acquisition of cancer cell chemoresistance with mutatedTP53and MDM2 up-regulation

Abstract: Keywords: apoptosis, heat shock protein (HSP), mutant p53 gain-of-function, mouse double minute 2 homolog (MDM2),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 110 publications
0
33
0
Order By: Relevance
“…Moreover, CTM restores MDM2’s ability to induce mutp53 degradation. Additionally, Tracz-Gaszewska et al [100] observe that DNAJB1 and HSP70 facilitate binding of mutp53 (V143A, R158L, R175H, Y220C, G245S, D281G, R282W) to TAp73α. Another HSP40 member that plays a role in stabilization of mutp53 is DNAJA1.…”
Section: Molecular Chaperonesmentioning
confidence: 99%
“…Moreover, CTM restores MDM2’s ability to induce mutp53 degradation. Additionally, Tracz-Gaszewska et al [100] observe that DNAJB1 and HSP70 facilitate binding of mutp53 (V143A, R158L, R175H, Y220C, G245S, D281G, R282W) to TAp73α. Another HSP40 member that plays a role in stabilization of mutp53 is DNAJA1.…”
Section: Molecular Chaperonesmentioning
confidence: 99%
“…This results in a loss of p73-mediated transcription and a gain in p63-mediated transcription [46,57]. Interestingly, a closer examination of the mutant p53-p73 complex further revealed that other HSP family members can also interact with the complex and that MDM2 can replace the HSP proteins to form a more stable complex and potentiate chemoresistance [58].…”
Section: Functional Consequences and Binding Partners Of Mutant P53-tmentioning
confidence: 99%
“…Moreover, it was shown recently that HSPs are involved in the evolution of cancer cells resulting in tumor heterogeneity. Such evolution could be accelerated by the chemotherapy and could lead to the acquisition of chemoresistance 11,21,22 . In contrast, some research has shown that reduced expression of HSPs is associated with poor prognosis in cancer patients 23,24 .…”
Section: Introductionmentioning
confidence: 99%